Dataset for estimation of muscle Dysmorphia in individuals from Colombia (2020)
This paper presents data collected through a questionnaire for the estimation of body dysmorphic disorder known as vigorexy, weight level and levels of exercise dependence in individuals from Barranquilla, Colombia who attend local gyms, based on their physical activity, food supplements eat- ing habits, psychological pressure, and risk of muscle dys- morphia. The Data contains 8 tributes and 200 records; la- belling obesity range according to WHO into normal, over- weight or obesity. All data was collected in person and di- rectly from users. This data can be used to generate scien- tific research and intelligent computational tools to identify the obesity level and muscle dysmorphia risk of an individ- ual and to build recommender systems that monitor health and mental status.